PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN (Studi Pada Konsumen Toko Tong Hien Semarang) - Irwinda Amelita Rahmayani, 15.05.51.0059; Tjahjaningsih, Endang (Students' Journal of Economic and Management, 2019)
Today's world of trade is competition in marketing products or services. Marketing activities have a very important role in the business world, given their orientation towards society (consumers). Purchasing decisions are important to analyze because of the existence of a free market. This study aims to examine the effect of product quality, price perception, and location on consumer purchasing decisions in Tong Hien Semarang. The sampling method uses purposive sampling which is sampling with certain considerations so that the samples used in this study were 100 respondents. The data used is primary data. The data is obtained directly from consumers Tong Hien Semarang shop that has made a purchase through the questionnaire method (questionnaire). The primary data was analyzed by SPSS 22.0 software through an instrument test in the form of multiple linear regression tests, test coefficient of determination (R2) and F test, and hypothesis testing in the form of t test. The results of this study indicate that partially, product quality variables have a positive and significant effect on purchasing decisions, price perception variables have a positive and significant effect on decisions, location variables have a positive and significant effect on purchasing decisions.